The basics : a rhetoric and handbook - Buscemi, Santi V.; Nicolai, Albert H.; Strugala, Richard (Boston, Mass. : Irwin/McGraw-Hill, 1998)
Language and Literature
Keywords: English language; English language-Rhetoric; English language-Grammer; Report writing-Handbooks, manuals, etc.; Writing skill; Drafting; Editing